PENGARUH TENURE, UKURAN KAP DAN SPESIALISASI AUDITOR TERHADAP KUALITAS AUDIT - Clinton Marshal Panjaitan; Anis Chariri (Diponegoro Journal of Accounting, 2014)
This study aimed to empirically examine the effect of audit tenure, the size of the public accounting firms, and auditor specialization on audit quality. The population of the data is the entire manufacturing companies listed on the Indonesia Stock Exchange in the period 2010 to 2012. This study used purposive sampling method to select sample from the population. Based on this method, sample of 193 manufacturing firms were obtained from the period 2010-2012. The multiple linear regression was used to analyse data. Proxy measurements for audit quality is using discretionary accrual Kazsnik model (1999). The results showed that audit tenure negatively affecting on audit quality and auditor specialization positively affecting on audit quality, while the size of public accounting firms has no effect on audit quality.